Cadavres féminins et fictions policières contemporaines - Maud Desmet (Socio-anthropologie, 2015)
Whether it be on autopsy tables or on crime scenes, the corpse—this ambivalent absence/presence figure which crime narratives need to be structured, is predominantly feminine. This feminine figure incarnating the eternal tortured victim is submitted to a particular treatment, differing from that of the masculine corpse. The feminine corpse, because it reunites two territories both enigmatic and potentially threatening to men—femininity and death—is a troubling object. In crime fictions, the staging of a feminine corpse can take the most poetic shape, through the resurgence of the myth of Ophelia, reassuring the audience in their “romantic” vision of female death. But when its staging abandons its poetic attires, only leaving a tortured corpse, its necessarily threatening—on a symbolical level—abjection must then be defeated or contained by the living male characters gravitating around it.